Catalytic Transformation of PET and CO2 into High‐Value Chemicals. (25th January 2022) - Li, Yinwen; Wang, Meng; Liu, Xingwu; Hu, Chaoquan; Xiao, Dequan; Ma, Ding
Abstract: Polyethylene terephthalate (PET) and CO2, two chemical wastes that urgently need to be transformed in the environment, are converted simultaneously in a one‐pot catalytic process through the synergistic coupling of three reactions: CO2 hydrogenation, PET methanolysis and dimethyl terephthalate (DMT) hydrogenation. More interestingly, the chemical equilibria of both reactions were shifted forward due to a revealed dual‐promotion effect, leading to significantly enhanced PET depolymerization. The overall methanol yield from CO2 hydrogenation exceeded the original thermodynamic equilibrium limit since the methanol was in situ consumed in the PET methanolysis. The degradation of PET by a stoichiometric ratio of methanol was significantly enhanced because the primary product, DMT was hydrogenated to dimethyl cyclohexanedicarboxylate (DMCD) or p‐xylene (PX). This synergistic catalytic process provides an effective way to simultaneously recycle two wastes, polyesters and CO2, for producing high‐value chemicals. Abstract : Polyethylene terephthalate (PET) and CO2, two chemical wastes that urgently need to be transformed in our environment, are converted simultaneously in a one‐pot catalytic process. The process for dual‐promoted conversion overcomes the original thermodynamic equilibrium limits of methanol synthesis and PET methanolysis, leading to a significantly enhanced yield of PET.